A Systematic Review and Meta-Analysis on the Effect of Nature Exposure Dose on Adults with Mental Illness - Joanna Ellen Bettmann; Elizabeth Speelman; Annelise Jolley; Tallie Casucci (Behavioral Sciences)
Time spent in nature leads to significant physical and mental benefits, but research is mixed on how much time in nature is necessary to affect change in adults’ mental health. This meta-analysis aimed to answer the question: what effect does length and interval of nature dosage have on adults with mental illness? The authors defined nature exposure as an experience in nature lasting at least 10 minutes and taking place in an actual natural setting. Because some studies indicated single experiences of exposure to nature (one-time) while others utilized multiple exposures to nature (interval), these studies were separated to determine differences between one-time versus interval exposure to nature. Following Cochrane Handbook for Systematic Reviews of Interventions and PRISMA reporting guidelines, this review included 78 studies published between 1990 and 2020. The present study found that one-time and interval nature exposure yielded different results for adults with a diagnosed mental illness and adults with symptoms of mental illness. Notably, shorter nature exposure delivered in intervals appeared to show positive significant effects, even more than one-time exposure. This finding has important implications for public health and green space preservation, as being outside for as little as 10 minutes and even in urban nature can improve adults’ mental health.